Pseudo concurrent quad-band LNA operating in 900 MHz/1.8 GHz and 900 MHz/2.4 GHz bands for multi-standard wireless receiver - Datta, Sambit; Dutta, A.; Datta, K.; Bhattacharyya, T. (2011)
This article presents the design of a novel quad-band LNA operating in the GSM 0.9GHz/GSM l.8GHz and ZigBee 0.9GHz/WLAN 2.4GHz communication standards. This pseudo-concurrent architecture uses a one bit mode switch for selecting between the frequency bands. An RF switch is implemented before the Low Noise Amplifier (LNA) module to improve the insertion loss and isolation between the frequency bands. A design methodology for the selection of output matching load network has been proposed .The pseudo-concurrent LNA is designed and simulated in CADENCE using 130nm UMC technology. The current design is especially suitable for use in multi-standard wireless receiver frontends as it saves die area and reduces power consumption by replacing parallel LNAs for each channel frequency. Simulation results indicate a Noise Figure below 4dB and S21 above 14 dB in all frequency bands while drawing 10mA current from a 1.2V power supply. © 2011 IEEE.